An Appraisal of Public Infrastructure Project Procurement: Focus on Transparency Provisions in the Nigerian Procurement Act - Eze, G. C.; Ogunsina, O.; Igwe, J. C. (International Journal of Real Estate, 2025)
This paper evaluates the degree of transparency in the PPA 2007 and its effectiveness and compliance with globally acceptable standards. Efficiency in public procurement systems has been established to enhance service delivery and reduce opportunities for corruption. Despite the Procurement Practice Act’s (PPA) strategies, such as open bidding, public bid opening sessions, and provision of procurement information, implementation challenges include accessibility, lack of specificity in evaluation rubrics, and poor complaint handling. The mixed method research techniques were utilized in the study. This includes case studies, surveys, and a literature review. The most important observations made by respondents and stakeholders were that there is a great awareness of the act’s existence but there are issues that bedevil its successful implementation. This study points to the gaps between enacting the law and its execution such as inadequate or delayed publication of awarded contracts and lack of efficient e-procurement systems. Some of the international standards on the use of technology and management of conflict of interest in procumbent processes and systems are particularly revealing of how Nigeria has fallen behind. The study concludes that PPA, 2007 has a relatively good base for transparency, However, its practicality is ineffective due to a lack of enforcement, political interference, and a lack of technological integration.